GCG inhibits SARS-CoV-2 replication by disrupting the liquid phase condensation of its nucleocapsid protein - Ming Zhao (Nature Portfolio, 2021)
Coronavirus nucleocapsid (N) protein is important for viral genome packaging and virion assembly. Here the authors show that natural chemical (-)-gallocatechin gallate (GCG) disrupts the liquid–liquid phase separation of N and inhibits SARS-CoV-2 replication.